What Types of Instructional Shifts Do Students Experience? Investigating Active Learning in Science, Technology, Engineering, and Math Classes across Key Transition Points from Middle School to the University Level - Akiha, Kenneth; Brigham, Emilie; Couch, Brian A.; Lewin, Justin; Stains, Marilyne; Stetzer, MacKenzie R.; Vinson, Erin L.; Smith, Michelle K. (Frontiers in Education, 2018)
Despite the need for a strong Science, Technology, Engineering, and Math (STEM) workforce, there is a high attrition rate for students who intend to complete undergraduate majors in these disciplines. Students who leave STEM degree programs often cite uninspiring instruction in introductory courses, including traditional lecturing, as a reason. While undergraduate courses play a critical role in STEM retention, little is understood about the instructional transitions students encounter upon moving from secondary to post-secondary STEM courses. This study compares classroom observation data collected using the Classroom Observation Protocol for Undergraduate STEM (COPUS) from over 450 middle school, high school, introductory-level university, and advanced-level university classes across STEM disciplines. We find similarities between middle school and high school classroom instruction, which are characterized by a large proportion of time spent on active-learning instructional strategies, such as small-group activities and peer discussion. In contrast, introductory and advanced university instructors devote more time to instructor-centered teaching strategies, such as lecturing. These instructor-centered teaching strategies are present in classes regardless of class enrollment size, class period length, or whether or not the class includes a separate laboratory section. Middle school, high school, and university instructors were also surveyed about their views of what STEM instructional practices are most common at each educational level and asked to provide an explanation of those perceptions. Instructors from all levels struggled to predict the level of lecturing practices and often expressed uncertainty about what instruction looks like at levels other than their own. These findings suggest that more opportunities need to be created for instructors across multiple levels of the education system to share their active learning teaching practices and discuss the transitions students are making between different educational levels.